Antiproliferative Effect of Chloroform Extract of Cangkring Leaves (Erythrina fusca Lour.) and Its Isolates against Hela Cells - Puspitasari, Endah; Setyowati, Endah Dwi; Dhiani, Binar Asrining; Riyanto, Sugeng (Indonesian Journal of Cancer Chemoprevention, 2012)
Cervical cancer is a type of cancer possessing the 3rd highest incidence among women worldwide. Todays therapies against cancer are still ineffective, thus people are seeking for alternative method. Erythrina fusca Lour. has been used traditionally as anticancer. This experiment is conducted to study the ability of chloroform extract of E.fusca Lour. leaves and its isolates on HeLa cervical cancer cells. The cytotoxicity assay and doubling time assay were done using direct counting method, while the DNA staining assay was done using acrydine orange. The chloroform extract and isolate #30 showed cytotoxic activity with IC50 of 16 and 5 Î¼g/ml, respectively, while isolate #2 and isolate #8 didnt. The effluent #30 could not affect HeLa cells growth at the given concentration, but it might promote DNA fragmentation indicating apoptosis induction. The molecular mechanisme underlying these effects still need to be further explored.Keywords : Â Erythrina fusca Lour., isolate and effluent of chloroform extract, antiproliferative, cervical cancer